3D-Assisted Quantitative Assessment of Orbital Volume Using an Open-Source Software Platform in a Taiwanese Population - Shyu, Victor Bong-Hang; Hsu, Chung-En; Chen, Chih-hao; Chen, Chien-Tzung (PloS one, 2015)
Orbital volume evaluation is an important part of pre-operative assessments in orbital trauma and congenital deformity patients. The availability of the affordable, open-source software, OsiriX, as a tool for preoperative planning increased the popularity of radiological assessments by the surgeon. A volume calculation method based on 3D volume rendering-assisted region-of-interest computation was used to determine the normal orbital volume in Taiwanese patients after reorientation to the Frankfurt plane. Method one utilized 3D points for intuitive orbital rim outlining. The mean normal orbital volume for left and right orbits was 24.3±1.51 ml and 24.7±1.17 ml in male and 21.0±1.21 ml and 21.1±1.30 ml in female subjects. Another method (method two) based on the bilateral orbital lateral rim was also used to calculate orbital volume and compared with method one. The mean normal orbital volume for left and right orbits was 19.0±1.68 ml and 19.1±1.45 ml in male and 16.0±1.01 ml and 16.1±0.92 ml in female subjects. The inter-rater reliability and intra-rater measurement accuracy between users for both methods was found to be acceptable for orbital volume calculations. 3D-assisted quantification of orbital volume is a feasible technique for orbital volume assessment. The normal orbital volume can be used as controls in cases of unilateral orbital reconstruction with a mean size discrepancy of less than 3.1±2.03% in females and 2.7±1.32% in males. The OsiriX software can be used reliably by the individual surgeon as a comprehensive preoperative planning and imaging tool for orbital volume measurement and computed tomography reorientation.